2007
DOI: 10.1007/s00246-007-9166-z
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Courses of Indomethacin and Neonatal Outcomes in Premature Infants

Abstract: The objective of this retrospective cohort study was to determine patent ductus arteriosus (PDA) closure rate with multiple short courses (three doses) of postnatal indomethacin and compare neonatal outcomes in infants who received two versus three courses of indomethacin for PDA closure. Infants <34 weeks' gestational age born between January 2000 and December 2004 at the University of Maryland Medical Center and who received two or more short courses of indomethacin were included. Outcome measures were ducta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…The degree of hypoxia and its duration are all important when considering possible tissue damage. A recent study by Sangem et al [16] showed an increase in periventricular leukomalacia associated with repeated courses of indomethacin. This could be explained by the effect of indomethacin on the cerebral blood flow discussed earlier.…”
Section: Discussionmentioning
confidence: 99%
“…The degree of hypoxia and its duration are all important when considering possible tissue damage. A recent study by Sangem et al [16] showed an increase in periventricular leukomalacia associated with repeated courses of indomethacin. This could be explained by the effect of indomethacin on the cerebral blood flow discussed earlier.…”
Section: Discussionmentioning
confidence: 99%
“…But in the same study a higher incidence of periventricular leucomalacia was noted in those receiving the third course. This may be due to the well‐established vasoconstrictive effects of indomethacin, or the results may well have been confounded by the cohort of sicker neonates with associated comorbidities who failed to respond to the first two courses …”
Section: Pharmacotherapymentioning
confidence: 99%
“…However, a higher increase of periventricular leukomalacia in those who received a 3 rd course of indomethacin does raise some concern. Like Indomethacin, the closure rate of PDA after a second or third course of ibuprofen was similar to the closure rate after the first course but not associated with an increase in adverse effects [54].…”
Section: Dose and Administrationmentioning
confidence: 63%
“…In a retrospective study, Sangem et al [53,54] observed a 42% response rate after a second course of indomethacin and a 43%, with the third course of indomethacin, yielding a cumulative response rate to 3 courses of indomethacin of 90%. However, a higher increase of periventricular leukomalacia in those who received a 3 rd course of indomethacin does raise some concern.…”
Section: Dose and Administrationmentioning
confidence: 99%